ANALYSIS OF JUDGES' CONSIDERATIONS IN DECIDING EMBEZZLEMENT CASES (Study of Decision Number 65/Pid.B/2024/PN. Sbr) - Dadan Taufik Fathurohman; Rafa Rizqullah; Safina Ni’mah Azzahra; Wahyu Bassevi Putra (Jurnal Abdisci, 2025)
Abstract Background. The Indonesian Criminal Code regulates criminal acts and criminal sanctions based on the crime or violation committed. The crime of embezzlement is one of the most common. Embezzlement is hiding someone else's property without the owner's knowledge with the intention of controlling or using it for other purposes. Aims. In this study, we discuss the crime of embezzlement, especially that related to work, and the judge's consideration when making decisions about decision No. 65/Pid.B/2024/PN. Sbr. Normative and empirical juridical research methods are used, and the embezzlement of Article 372 of the Criminal Code shows that the elements are fulfilled in this case. Methods. This study used normative juridical methods and case study approaches (Decisions). Some sources, namely primary and secondary legal materials, are sourced from the study of applicable laws and regulations and are relevant to decision No. 65/Pid.B/2024/PN. Sbr. They are also supported by literature studies, document studies, journals, and other sources that contain matters relevant to the study of this decision. Result. The application of material criminal law to embezzlement in employment relations No. 65/Pid.B/2024/Sbr. In our opinion, it fulfills Article 372 of the Criminal Code. In article 374 of the Criminal Code, the element of the crime of embezzlement of office is not fulfilled, because Oman's brother, Abdul Rochman Bin Badri (Alm), does not work as an employee in Deni Purwanto's company. Conclusion. The judge decided that there is no legal evidence of embezzlement in office as in the primary indictment of the Public Prosecutor, that this case is a civil dispute. Implementation. It would be good to file this case civilly as stated in Article 1865 of the BW.